Evaluation of the antimicrobial management of intracranial suppurative infections in a single pediatric institution - Cameron E. Bizal; Alaina N. Burns; Rana E. El Feghaly; Brian R. Lee; Ann L. Wirtz (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract